2022
DOI: 10.3390/su142416402
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Symptom-Specific Anxiety in Chinese Preschoolers: The Role of Maternal Anxious Rearing Behaviors

Abstract: Although developmental trajectories of anxiety have begun to be explored, most research has focused on total anxiety symptom scores in middle childhood and adolescence. Little is known about the developmental trajectories of specific anxiety symptoms in early childhood. This three-wave longitudinal study investigated (1) the developmental trajectories of four specific anxiety symptoms (separation anxiety, special fear, social anxiety, and generalized anxiety) during early childhood, and (2) the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Contribution 8 followed the development of four specific anxiety symptoms in young children over time and found that these symptoms changed according to the typical challenges in different stages of child development [9]. The authors also looked at how maternal anxious rearing behaviors were related to children's anxiety symptoms from a developmental point of view.…”
Section: Sustainable Development Of Young Children and Their Familiesmentioning
confidence: 99%
“…Contribution 8 followed the development of four specific anxiety symptoms in young children over time and found that these symptoms changed according to the typical challenges in different stages of child development [9]. The authors also looked at how maternal anxious rearing behaviors were related to children's anxiety symptoms from a developmental point of view.…”
Section: Sustainable Development Of Young Children and Their Familiesmentioning
confidence: 99%